The effect of perceived social support and achievement motive on hopelessness - Horino, Midori; Mori, Kazuyo (Shinrigaku kenkyū, 1997)
The purpose of this study was to investigate the effect of achievement motive on the relationship between perceived social support and hopelessness in elementary school children. Two surveys were administered. The first examined the reliability and validity of an achievement motive scale with 273 4th through 6th graders children. The second examined the joint effect of achievement motive and perceived social support on the tendency to feel hopeless, with 410 children of the same age group. Results confirmed that the two-factor structure was indeed appropriate for an achievement motive scale, and that self-fulfilment achievement motive was a moderating variable of the relationship between perceived social support and hopelessness.